Allele frequencies and forensic parameters of 22 autosomal STR loci in a population of 983 individuals from Serbia and comparison with 24 other populations - Dijana Takić Miladinov; Perica Vasiljević; Dejan Šorgić; Eva Podovšovnik Axelsson; Aleksandra Stefanović (Taylor & Francis Group, 2020)
Background Analysis of allele frequencies of short tandem repeat (STR) loci in ethnically diverse populations is essential for forensic reference database construction and studies on population genetics. Aim To analyse genetic polymorphisms of 22 autosomal STR loci in the Serbian population and to compare them with previously published data from some European and Turkish populations. Subjects and methods The study was conducted among 983 unrelated individuals from Serbia. Genotyping was performed using the PowerPlex® Fusion amplification kit. Allele frequencies and forensic parameters were calculated using FORSTAT software. Interpopulation comparisons and genetic distance calculations were performed in Arlequin and POPTREEW software. Results A total of 280 alleles were detected with corresponding allelic frequencies ranging from 0.0005 to 0.5255. Based on heterozygosity and the polymorphism information content, D1S1656 and Penta E may be considered as the most informative markers. Both the combined power of discrimination (CPD) and the combined power of exclusion (CPE) for the 22 analysed loci were higher than 0.999999. The combined match probability (CPM) for all 22 loci was 6.773688e−29. Conclusion With respect to the results, the 22 STR loci are highly polymorphic and discriminating in the Serbian population and could be used for forensic practice and population genetics studies.